1978
DOI: 10.1038/271329a0
|View full text |Cite
|
Sign up to set email alerts
|

X–chromosome inactivation during differentiation of female teratocarcinoma stem cells in vitro

Abstract: Evidence is presented that both X chromosomes are genetically active in clonal cultures of undifferentiated female mouse teratocarcinoma stem cells derived from a spontaneous ovarian tumour. As the cells differentiate in vitro one of the X chromosomes becomes inactivated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
39
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 29 publications
3
39
0
Order By: Relevance
“…Fitting for this meeting though, was the fact that no in vitro model existed for this process before the derivation of EC cell lines. Using a female teratocarcinoma cell line, Gail Martin (Martin et al, 1978) revealed X-chromosome inactivation during differentiation, a finding later confirmed in mouse ES cells. However, it should be noted that this is considered the second 'random' wave of X-inactivation.…”
Section: Characterisation Of Pluripotent Cellsmentioning
confidence: 79%
“…Fitting for this meeting though, was the fact that no in vitro model existed for this process before the derivation of EC cell lines. Using a female teratocarcinoma cell line, Gail Martin (Martin et al, 1978) revealed X-chromosome inactivation during differentiation, a finding later confirmed in mouse ES cells. However, it should be noted that this is considered the second 'random' wave of X-inactivation.…”
Section: Characterisation Of Pluripotent Cellsmentioning
confidence: 79%
“…Thus, although the normal differentiation of the X chromosome requires its inactivation rather than activation (27), the induction of HPRT synthesis in the highly-selectable HAT system should allow us to address further questions to the control of cellular differentiation through the cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphoglycerate kinase (PGK), glucose-6-phosphate dehydrogenase (G6PD), and HPRT isozyme analyses were performed with cell lysates prepared as previously described (19). Electrophoretic separations were performed with Cellogel (Kalex Scientific).…”
mentioning
confidence: 99%